Disposition to risk and impulsive actions in athletes of different ages - Babii, Mykola; Duchyminska, Tamara; Kots, Mykhailo (Psychological Prospects Journal, 2023)
Purpose. Empirical study of the propensity of athletes of different ages to risk, impulsive actions and their control.Methods. In order to achieve the goal, we compiled a research program, which included three diagnostic tools: A. Shmelov's "Investigation of Risk Propensity" method, V. A. Losenkov's Test-Questionnaire "Investigation of Impulsivity", Questionnaire "Action Control Scale".Results. The obtained results indicate that all age categories involved in our empirical study have a high propensity to risk. The only difference is that supporters of individual sports are more inclined to such actions, especially those who attend such sports sections as: wrestling (karate, judo), types of boxing, hand-to-hand combat, when decision-making is dictated by the situation in the ring, tatami. Undoubtedly, before the fight, each of the opponents receives certain instructions from the coach, but his dynamics often do not go according to the script, and then you have to take risks. Supporters of collective species also receive an installation for a meeting with an opponent. They receive certain instructions for the match from the sports coach, so the team tries to follow a certain scenario of the game, where everyone is assigned a certain role. Therefore, taking risky actions means "breaking the established scheme" and receiving reprimands from teammates and the coach. Accordingly, athletes of team sports are less prone to risk.Studies of propensity to impulsive actions indicate that representatives of three age groups have an average level of propensity to impulsive actions, i.e., individuals of adolescent, early youth, and youth age are prone to moderate deliberate actions regardless of sports. The only thing that distinguishes a group of teenagers from older people is that among them there are more people with a high level of propensity for such actions. This can be explained by the peculiarities of age, because the high activity of the glands of internal secretion leads to a loss of balance between the processes of excitation and inhibition. Therefore, people of this age have poor control over their own actions and speech.In the control of actions, we noticed the following differentiation: fans of individual sports are more inclined to control the action during planning, because in training they practice more body blows or certain wrestling techniques that they will later apply in practice; athletes in team sports prefer to control actions during implementation, in this way they perform game setup when they practice before the game itself. It is worth noting that all age groups have a rather low control during failures, because they set themselves up only for victory.Conclusions. The conducted empirical research confirms the effectiveness of the proposed diagnostic program for risk, impulsive actions and their control. Our next research will be to study the influence of the emotional state on the athlete's performance during the competition.